The Effect of Cone Training and Backcourt Sessions on the Agility of Squash Athletes - Nugraha Pratama; Tatang Muhtar; Dinar Dinangsit (UNIB Press, 2024)
In squash, Agility is the ability to move various footsteps and aim to place the body position as quickly as possible. This study aims to determine the effect of Cones Drill and BackCourt exercises on increasing agility in squash. The method used in this study is a quasi-experimental method using pretest posttest control group design. The population in this study was 76 people from all over West Java Squash athletes, a sample of 22 squash athletes in Sumedang district using purposive sampling techniques. Before collecting data, researchers were divided into 2 groups using the ABBA technique. The data collection technique was carried out by conducting initial tests using the Illinois Agility Run to 2 groups. Then given the Cones Drill and Backcourt Session exercise treatment, then given a final test using the illinois agility run. for data processing techniques, descriptive statistical analysis and comparative test analysis which shows that, (1) There is a significant influence on increasing agility in squash sports with the Cones Drill training method. (2) There is a significant effect on increasing agility in squash with the BackCourt Session training method. (3) There is no significant difference in the effect between Cones Drill training methods and BackCourt Session training on the ability to increase agility in squash. The practice method of cone drill drills and backcourt sessions has an influence on improving agility, both methods have a very significant influence. So it can be concluded that Cones drill and backcourt practice methods have an equally important influence in improving agility in the sport of squash.